Оцінка стану здоров’я дорослого населення зони спостереження Запорізької Атомної Електростанції = Evaluation of health status of adult population in the observation area of Zaporizhia Nuclear Power Plant - Khomenko, I. M.; Zakladnaya, N. V. (Journal of Education, Health and Sport, 2016)
Khomenko I. M., Zakladnaya N. V. Оцінка стану здоров’я дорослого населення зони спостереження Запорізької Атомної Електростанції = Evaluation of health status of adult population in the observation area of Zaporizhia Nuclear Power Plant. Journal of Education, Health and Sport. 2016;6(2):77-86. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45847 http://ojs.ukw.edu.pl/index.php/johs/article/view/3379 https://pbn.nauka.gov.pl/works/713314 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.01.2016. Revised 12.01.2016. Accepted: 31.01.2016. УДК 613:614.876:340.13(477) Оцінка стану здоров’я дорослого населення зони спостереження Запорізької атомної електростанції Evaluation of health status of adult population in the observation area of Zaporizhia Nuclear Power Plant 1І. М. Хоменко, 2Н. В. Закладна 1I. M. Khomenko, 2N. V. Zakladnaya 1НМАПО імені П. Л. Шупика, 2Токмацьке міжрайонне управління Держсанепідслужби у Запорізькій області 1Shupyk National Medical Academy of Postgraduate Education, 2Tokmak Interregional Administration of Sanitary and Epidemiological Service of Zaporizhia Region Abstract Introduction. Exploitation of nuclear power plants (NPP) is accompanied by a specific radiation and non-radiation influence on the environment. That is why the detection of their influence on the health of adjacent areas residents is of great importance. Objective. To estimate health status of the population of observation area of nuclear power facilities ofUkraineon the example of Zaporizhia NPP. Materials and methods. System review, bibliographic, analytical and statistical methods are used in the research. Results. An increase in the disease incidences of the digestive system of the adult population was found in certain regions of Zaporizhia NPP observation area. Conclusions. In connection with further development of nuclear power engineering and extension of nuclear power plants inUkraineafter the end of their operation lifetime and possible influence of adverse environmental factors during their exploitation for health of population dwelling on the observation area, the morbidity of population requires more detailed study and estimation. Key words: nuclear power plants, radiation protection, observation area, morbidity of population. Реферат Оценка состояния здоровья взрослого населения в зоне наблюдения Запорожской атомной электростанции. Введение. Эксплуатация атомных электростанций (АЭС) сопровождается как специфическим радиационным, так и нерадиационным воздействием на окружающую среду. Поэтому изучение их влияния на здоровье жителей близлежащих территорий является актуальным. Цель. Оценить состояние здоровья населения в зоне наблюдения объектов атомной энергетики Украины на примере Запорожской АЭС. Материалы и методы. Использованы системно-обзорный, библиографический, аналитический и статистический методы. Результаты. Установлен рост заболеваемости взрослого населения отдельных районов зоны наблюдения Запорожской АЭС болезнями органов пищеварения. Выводы. В связи с перспективой дальнейшего развития ядерной энергетики и продления действующих АЭС после окончания проектного срока их эксплуатации в Украине и возможным воздействием вредных факторов при их эксплуатации на здоровье населения, проживающего в зоне наблюдения, заболеваемость населения требует более детального изучения и оценки. Ключевые слова: атомные электростанции, противорадиационная защита, зона наблюдения, заболеваемость населения. Реферат Вступ. Експлуатація атомних електростанцій (АЕС) супроводжується як специфічним радіаційним, так і нерадіаційним впливом на навколишнє середовище. Тому вивчення їх впливу на здоров’я жителів прилеглих територій є актуальним. Мета. Оцінити стан здоров’я населення зони спостереження об’єктів атомної енергетики України на прикладі Запорізької АЕС. Матеріали та методи. Використані системно-оглядовий, бібліографічний, аналітичний та статистичний методи. Результати. Встановлено зростання захворюваності дорослого населення окремих районів зони спостереження Запорізької АЕС на хвороби органів травлення. Висновки. У зв’язку з перспективою подальшого розвитку ядерної енергетики й подовження роботи діючих АЕС після закінчення проектного терміну їх експлуатації в Україні, можливим впливом шкідливих чинників при їх експлуатації на здоров’я населення, яке мешкає в зоні спостереження, захворюваність населення потребує більш детального вивчення та оцінки. Ключові слова: атомні електростанції, протирадіаційний захист, зона спостереження, захворюваність населення.